Дослідження комбінування навчання з підкріпленням та мовних агентів для реалізації діалогових агентів - Бовдуй, Р. В. (ХНУРЕ, 2024)
The chatbot market has been growing rapidly lately. They allow you to optimize business processes and meet user needs. With the advent of large language models based on transformers, interest in the end-to-end approach to building such systems has increased. However, when building task-oriented dialog systems based on transformers, there is no certainty that they will pursue the intended goal, and here reinforcement learning comes to the rescue. The paper discusses the combination of these approaches in order to improve the characteristics of task-oriented dialogue systems which are needed for business.
Keywords: мовний агент; діалоговий агент